Experimental Research Methods“Anava and Factorial Experiment Psychology Research Design” - Bima Nanda Pratama; M. Luthfi Reza Putra; Nurhaliza (Psikologiya Journal, 2024)
The experimental research method is an approach used to examine the effect of certain treatments on other variables under controlled conditions. In experiments, researchers manipulate a stimulus or treatment, then observe its impact on the variable under study. This research discusses experimental design and its purpose, including ANOVA and factorial experimental psychology research designs. Experimental design allows researchers to test hypotheses with well-defined steps before conducting experiments. There are several types of experimental designs, including pre-experimental, true experimental, factorial experimental, and quasi-experimental. Analysis of Variance (ANOVA) is a statistical method for comparing the means of several groups of data with respect to their variances. Factorial design involves the simultaneous manipulation of several factors to study the effect on the dependent variable. This study describes the characteristics, objectives, and types of factorial designs as well as their advantages and disadvantages. The experimental design and statistical analysis used help researchers understand and analyze data more comprehensively and objectively